PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN KEBIJAKAN DIVIDEN TERHADAP KEBIJAKAN HUTANG PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Tamba, Romega; Yusran, Rio Rahmat (SCIENTIA JOURNAL, 2019)
This research was conducted to test and analyze the influence of managerial ownership, institusional owrnership and dividend policy on debt policy of companies listed on the IDX. The independent variable are managerial ownership, institusional owrnership and dividend policy. The population in the study is a food and beverage sub-sector manufacturing company listed on the IDX 2013-2017 hypothesis testing carried out using statistical test namely F test and t-test. Of the 18 companies, 8 companies have met the criteria to be used as research samples. This the data analyzed amounts to 40. Managerial ownership has a significant effect on the company’s debt policy with a significant value of 0,00< 0,05. Institusional ownership has a significant influence on the company debt policy with a significant value of 0.254< 0,05. Dividend policy has a significant influence on corporate debt policy with a significant value of 0,05< 0,05. Jointly managerial ownership, institusional ownership and dividend policy towards the company’s debt policy, with a significant value of F 0,000< 0,005. From the result of the test R square has a value of 41.8% while the remaining 58.2%